'Made in China 2025': Poised for Success?. (September 2021) - Agarwala, Nitin; Chaudhary, Rana Divyank
In the last 70 years, due to reforms and policies, China has moved from an agrarian economy to being a manufacturing superpower. However, this has been possible due to technology transfers into China with the core technologies remaining with the West in the name of competitiveness and national security. To achieve true technological independence and self-reliance, China proposed the 'Made in China 2025' policy in 2015 which has since been opposed vehemently by the West. This notwithstanding, China has continued its effort of self-reliance. Hence, it is essential to evaluate if these efforts are bearing the required results. Using qualitative research, the authors look at the factors leading China to adopt 'Made in China 2025' and the opposition faced by it through tariff and non-tariff measures. Various supporting policies of Made in China 2025 (MIC25) and the advancements made have been examined. The article thus aims to address the ethos of initiating MIC25, the difficulties China is facing in realising its dreams due to restrictions by the US and its allies and how China is making an all-out effort to make it a success. The primary question that the article aims to answer is whether the efforts of China towards MIC25 are poised for success and how it will affect the developed nations.